HUBUNGAN PENGETAHUAN GIZI DENGAN SIKAP DALAM PEMILIHAN MAKANAN SEHAT PADA REMAJA DI AREA PEDESAAN - Ritma Dewanti; Syamsopyan Ishak; Suherman Rate; Hernianti Herman (Jurnal Ilmu Kebidanan, 2023)
Introduction:Teenagers generally choose unhealthy foods such as foods that are high in sugar, salt and fat, besides that the prevalence of teenagers consuming vegetables and fruit is relatively low. Adolescents make more food choices for themselves than children. One's knowledge will affect attitudes in choosing healthy foods.Objective:This study aims to analyze nutritional knowledge about risky foods with adolescent attitudes in determining food choices. Method: The research design used with designcross sectional. The sampling technique in this study used a multistage random sampling technique. The sample size in this study was 160 respondents with a population of 1143 selected from 10 high school/equivalent schools. The sample size was calculated using the OpenEpi software. Data analysis using testChi-Square. Results:The results showed that nutritional knowledge on attitudes had pvalue 0.026 (